2020
DOI: 10.12775/jehs.2020.10.09.047
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the occurrence of psoriasis and depression

Abstract: Proinflammatory cytokines such as interleukin (IL)-1 and IL-6 are elevated in both psoriasis and depression, indicating that the inflammatory process may be involved in the progression of both diseases. Psoriasis has long been recognized to be associated with potentially adverse effects on mental health. However, there have been relatively few studies evaluating psychological outcomes in patients with psoriasis. Depression and stress decrease the quality of life, psoriasis being the last drop in the glass, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Based on the results presented in this study, a decrease in quality of life was observed with an increase in AUDIT score and risk of alcohol dependence ( P <0.05) [ 57 ]. In addition, the risk of depression, lowered mood, lack of self-acceptance, and feelings of stigma are significantly worse among patients with psoriasis [ 57 ]. Thus, the negative impact of alcohol on the course of psoriasis, enzyme, psychological, and behavioral disorders was confirmed [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results presented in this study, a decrease in quality of life was observed with an increase in AUDIT score and risk of alcohol dependence ( P <0.05) [ 57 ]. In addition, the risk of depression, lowered mood, lack of self-acceptance, and feelings of stigma are significantly worse among patients with psoriasis [ 57 ]. Thus, the negative impact of alcohol on the course of psoriasis, enzyme, psychological, and behavioral disorders was confirmed [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the risk of depression, lowered mood, lack of self-acceptance, and feelings of stigma are significantly worse among patients with psoriasis [ 57 ]. Thus, the negative impact of alcohol on the course of psoriasis, enzyme, psychological, and behavioral disorders was confirmed [ 57 ]. These findings suggest the importance of conducting an in-depth interview with each patient and further AUDIT tests, as well as building an atmosphere of mutual understanding and non-stigmatization [ 57 ].…”
Section: Discussionmentioning
confidence: 99%